"رؤية العالم" في قراءة التراث البلاغي عند جابر عصفور - إكيدر, عبد الرحمان (قــــــراءات, 2019)
ظلت القراءة مفهوما أدبيا يصعب تحديده وتعريفه تعريفا دقيقا، وذلك لكونها عملية معقدة ومتشعبة تتداخل عناصرها وتتراكب، ومن هنا فإن هذا المصطلح يلفه عدد من الإشكالات سواء ما ارتبط بالنص المقروء أو الذات القارئة وتوجهاتها، إذ إن ذاتية القارئ وتذوقه وأدوات اشتغاله تلغي القراءة الواحدة وتفتح الآفاق أمام قراءات متعددة. فالقراءة لا تبدأ من فراغ أو من درجة الصفر. وقد انطلقت أبرز قراءات المحدثين للتراث البلاغي من هذا المنطلق، خصوصا قراءة جابر عصفور، والتي اتسمت بالنظرة الشمولية النسقية، المغترفة من منابع عدة، ساعية لكشف الأنساق المعرفية التي ساهمت في بلورة نصوص هذا التراث. وفي هذا الصدد، سنحاول الكشف عن نمط هذه القراءة التي تتوسل بمنظور "رؤية العالم" في قراءة التراث البلاغي العربي، وذلك من خلال إبراز إسهامات جابر عصفور في تأصيل هذه القراءة ومركزيتها في مشروعه النقدي. وسينصب التركيز في هذه الدراسة على مفهوم رئيس هو: "رؤية العالم" باعتباره آلية ناجعة تمكن من فهم أمثل لتلك النصوص. Abstract : Reading has always been a difficult concept to precisely define due to its complexity as a process whose elements integrate and overlap. Therefore, this concept remains with a number of problems either in the readable text or in the reader and his/her tendencies as his/her personality and preferences besides his/her tools of reading excludes one reading and opens horizons to different readings. It, then, does not begin from a vacuum. Thus, the most prominent modernist readings of the rhetorical heritage started from this principle, especially the reading of Gaber Asfour that is characterized by its comprehensive systematic outlook inspired from different sources seeking to uncover the knowledge patterns which contributed into the text elaboration of this heritage. In this regard, we try to reveal the patterns of this reading which relies on ‘the world vision’ perspective in reading the Arabic rhetoric heritage. This is done through highlighting the contributions of Gaber Asfour in authenticating this type of reading and its importance in his criticism project. The focus of this study is the world vision as as a viable tool to optimize the understanding of these texts.